RESEARCH INTO THE DEPICTION OF FAMILY IN RUSSIAN LITERATURE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Over the past centuries, the subject of family and family relations has been the object of study of psychology, philosophy, sociology, history and other humanities. The formation, development and crisis of family relationships have been manifested as one of the main themes in many works of art and literature. Especially in Russian literature, this topic is covered through deep psychological analysis. This article analyzes how Family Psychology is reflected in Russian literature, the authors ' approach to family relations and the role of the family in a socio-historical context.